Spark and sense: engaging do it yourself (DIY) sensory play content - Ja’afar Haris, Wan Alisa Maisarah; Daud, Derwina
Early childhood education plays a crucial role in shaping a child’s development, offering countless benefits that support their growth in many ways. Sensory play is one of the most impactful aspects of this process. It’s not just about keeping kids entertained, it actively helps improve their cognitive and critical thinking skills, language and communication abilities, and supports their social and emotional development. Dugan Laird’s research found that 75% of what adults learn comes from visual input, 13% from hearing, and the remaining 12% through touch, smell, and taste combined. This makes it clear how powerful sensory experiences are, especially for children. Giving them opportunities to engage in visual and multi-sensory activities can really enhance their learning. The main goal of this project is to help parents feel confident about introducing sensory play into their kids’ daily lives. The project aims to educate parents and provide them with easy DIY sensory play ideas they can try at home. It’s all about making sensory play simple, affordable, and enjoyable. By raising awareness and creating accessible resources, this project hopes to build a supportive community where parents can share ideas and encourage each other in fostering their children’s development through playful exploration.